Medical Ethics and Women Role in Robin Cook’s Coma and Fatal Cure - Shawawreh, Aysheh; Bani-Khair, Baker (Technium Social Sciences Journal, 2022)
Medical ethics are quite an essential and prevalent thematic issue in most of Robin Cook's novels. However, Robin Cook in his novels, Fatal Cure(1993) and Coma(1977) has presented a tremendous interest in the human ethical side which both novels constantly show in almost every single page. Robin intentionally brings contrasting images to show the importance of those roles that women play in medical professions. Ethics are the main drive towards any development, however, the two novels proposed a systematic approach in dealing with medical ethics by highlighting the focus on the frequent violation of ethical and moral law which are usually committed by psychologically disturbed individuals and psychopaths. This paper sheds light on the role that women play and the challenges they face to encounter and overcome those burdens in medical professions.